MODEL BISNIS PLAN DAN DAYA SAING UMKM MELALUI STRATEGI PEMASARAN PRODUK TERASI BAWANG DI INDRAMAYU - Nurpratama, Meddy; Yudianto, Agus (Jurnal Investasi, 2023)
The research entitled Behavioral model of MSME Processing Processed Onions and Tersi, Indramayu Regency. The purpose of this research is to explore and analyze the behavior of MSME actors processing agricultural products in Indramayu district and how the efforts are being made with business continuity MSME actors can apply or implement a business plan planning model, SWOT analysis, in dealing with business competition. The data collection method was carried out using interview techniques which were equipped with a semi-structured list of questions. The questionnaire was used as a guide so that interviews were more structured and standardized. The analysis technique that will be used is the concept of SWOT analysis is the concept of seeking analysis to determine a decision on a problem. SWOT itself is an acronym for Strength, Weakness, Opportunity, Treats. The term analysis of strengths and opportunities in preparing a business plan or and looking for weaknesses and strengths because in this concept all processes are carried out carefully and identify as much detail as possible so that decisions taken are effective and able to have a significant impact on dealing with problems